Prevalence and Description of Hyponatremia in a Swiss Tertiary Care Hospital: An Observational Retrospective Study - Lu, Henri; Vollenweider, Peter; Kissling, Sébastien; Marques-Vidal, Pedro (Frontiers in Medicine, 2020)
Background: Hyponatremia (serum sodium concentration <135 mEq/L) is the most common electrolyte abnormality among hospitalized patients. Our aim was to study the epidemiology of hyponatremia in hospitalized patients, as well as the short-term mortality rates, the length of stay (LOS) and associated hospital costs. Methods: This retrospective cohort study included 6539 hospitalizations in the internal medicine ward of a Swiss tertiary-care teaching hospital between January 1st 2012 and December 31st 2018 (42.7% women, mean age 69 years). Using serum sodium concentration, we identified hospitalizations with hyponatremia and calculated the prevalence of overall hyponatremia, admission hyponatremia (AH), hospital-acquired hyponatremia (HAH) and persistent hyponatremia (PH) at discharge. We also studied the impact of hyponatremia on 30-day readmissions, in-hospital and 30-day mortality and hospital LOS and costs, using multivariable logistic regression and Cox proportional hazards models, with normal natremia as reference. Results: Prevalence of overall hyponatremia was 32.5% (95% confidence interval (CI), 31.3-33.6%), while prevalence of PH among hospitalizations with AH and HAH was 33.7% (31.7-35.8%). After multivariable adjustment, hyponatremia was associated with increased hospital costs (CHF 19,025±485 vs. 14,962±341, p<0.001) and LOS (13.4±0.2 vs. 10.7±0.2 days, p<0.001). Increased severity of hyponatremia was associated with higher hospital costs and LOS (p for trend <0.001). There was a trend towards more frequent 30-day readmissions associated with hyponatremia (adjusted odds ratio (OR), 1.15 (1.01-1.31), p=0.032), mainly with PH: adjusted OR=1.41 (1.17-1.71), p<0.001. No association was found between severity of hyponatremia and readmissions. Hyponatremia was associated with an increase of in-hospital (adjusted OR=1.94 (1.49-2.53), p<0.001) and 30-day mortality: adjusted OR=1.80 (1.44-2.24), p<0.001. Increased severity of hyponatremia was associated with higher in-hospital and 30-day mortality (p for trend <0.001). Conclusions: Hyponatremia is highly prevalent among hospitalized patients, and associated with an increase of LOS, early hospital readmission, in-hospital and 30-day mortality and hospital costs. PH was associated with a substantial increase of the risk of early hospital readmission and 30-day mortality.